HUBUNGAN KOMUNIKASI BIDAN DENGAN TINGKAT KEPUASAN PASIEN PADA PELAYANAN KEBIDANAN ANTENATAL CARE (ANC) DI BIDAN PRAKTEKMANDIRI WILAYAH KERJA PUSKESMAS BOTANIA KOTA BATAM - Yenni Aryaneta; Mariyana Mariyana (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2017)
Good communication between midwife and pregnant mother greatly affect the satisfaction of pregnant mother in getting service by the midwife. So that can be obtained by mutual trust between midwives and patients. The purpose of this study is to know the relationship of midwives communication with the level of patient satisfaction in antiseptic midwifery care (ANC) in BPM Botania Puskesmas Working Area in 2017. This study used Cross-Sectional research design, the location of the study was conducted in BPM Botania Puskesmas Work Area and held on April-August 2017. The sample is a portion of pregnant women who come to visit to obtain ANC's ANC services in the Working Area of Botania Puskesmas with a total sample of 54 respondents. This research uses Purposive Sampling technique. The results of this study indicate that from 54 respondents midwives communicate both with 51 people (94.4%) and who are satisfied is as many as 50 people (92.6%) and bivariate analysis results obtained P-value 0.000 <0.05 means HO rejected, means there is a significant relationship between Communication Midwife With Patient Satisfaction Level on Antenatal Care Service Antenatal Care (ANC) in BPM Working Area of Botania Health Center Batam City Year 2017. Based on the above results, the researcher suggests to the medical personnel especially the midwife in order to further improve its ability in communicating so that patient feels satisfied with the obstetric care provided.